1989
DOI: 10.1093/bja/62.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Dose—response Curves for Suxamethonium in Neonates, Infants and Children

Abstract: Single dose-response curves were determined for suxamethonium in neonates, infants and children during thiopentone-fentanyl-nitrous oxide anaesthesia. During onset of neuromuscular block, suxamethonium produced an increase in muscle tone which was greatest in neonates and infants. The dose-response curves for the three groups were parallel. The effective doses producing 90% depression of twitch height were significantly greater in neonates and infants compared with children (517 and 608 v. 352 micrograms kg-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…Suxamethonium has been widely studied and used safely in infants including some studies based in neonatal units (10,23). The dose required for neonatal intubation, 2–3 mg·kg –1 , is higher than that required in adults which is partly due to a proportionally larger volume of distribution but may also be related to immaturity of the neuromuscular junction (86,87). Meakin et al .…”
Section: Neuromuscular Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…Suxamethonium has been widely studied and used safely in infants including some studies based in neonatal units (10,23). The dose required for neonatal intubation, 2–3 mg·kg –1 , is higher than that required in adults which is partly due to a proportionally larger volume of distribution but may also be related to immaturity of the neuromuscular junction (86,87). Meakin et al .…”
Section: Neuromuscular Blockersmentioning
confidence: 99%
“…Meakin et al . identified higher dose requirements in neonates and infants when compared to older children and suggested that associated muscle rigidity could be a result of underdosage (87).…”
Section: Neuromuscular Blockersmentioning
confidence: 99%
“…Suxamethonium can cause bradycardia, due to its action on the sinoatrial node, this response is exaggerated in children. 11,12 Inhalational induction e this is the preferred method in neonates and the alternative method in the event of unsuccessful intravenous cannulation. Good explanation to parent and child is again essential.…”
Section: B Inductionmentioning
confidence: 99%
“…Neugeborene und Säuglinge benötigen in mg/kg grö-ßere Dosen Succinylcholin [57] als Erwachsene (Abb. 2, Tabelle 4); äquipoten-te Dosen Succinylcholin wirken aber in allen Altersklassen ähnlich lang, obgleich die Aktivität der PChE im ersten Lebenshalbjahr noch kleiner ist.…”
Section: Succinylcholin In Der Kinderanästhesieunclassified